Postconviction Review of Jury Discrimination: Measuring the Effects of Juror Race on Jury Decisions - King, Nancy J. (1993)
As the Court has expanded its definition of jury selection techniques that violate constitutional standards, it has narrowed the circumstances that entitle defendants to postconviction relief. These two developments are now colliding; the emerging law is uncertain. One trend, however, is plain: divisions over the utility and propriety of applying harmless error, prejudice, and innocence standards to jury discrimination claims are deepening. By carefully evaluating the validity of some these disputes, I hope to have made remedial choices more informed and more attainable